2021
DOI: 10.1111/raq.12610
|View full text |Cite
|
Sign up to set email alerts
|

Review of shell waste reutilization to promote sustainable shellfish aquaculture

Abstract: Shellfish aquaculture has developed rapidly, and the annual production of shell waste by‐products exceeds 10 million tons. The reutilization of shell waste is a severe problem in terms of environmental protection and the development of the circular economy. Due to its limited economic value, shell waste has generally been discarded or sent to landfill without any further processing and reutilization, thereby wasting resources and severely degrading the coastal ecosystem. This review summarizes recent research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 85 publications
0
34
0
Order By: Relevance
“…However, it does not provide a solution to the demand for fossil fuels in the pretreatment of scallop shells. From the view of current research, the availability of scallop shells as waste from the extraction and cultivation of bivalve mollusks (aquaculture) creates a business opportunity to use them in the manufacture of various materials [48,50]. The availability of shells in a circular economy model creates a supply of raw materials and, at the same time, provides environmental relief by eliminating the need to dispose of scallop shells in landfills or dumps [78,79].…”
Section: Benefits/savings Related To the Use Of Caco3-constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it does not provide a solution to the demand for fossil fuels in the pretreatment of scallop shells. From the view of current research, the availability of scallop shells as waste from the extraction and cultivation of bivalve mollusks (aquaculture) creates a business opportunity to use them in the manufacture of various materials [48,50]. The availability of shells in a circular economy model creates a supply of raw materials and, at the same time, provides environmental relief by eliminating the need to dispose of scallop shells in landfills or dumps [78,79].…”
Section: Benefits/savings Related To the Use Of Caco3-constructionmentioning
confidence: 99%
“…The use of aquaculture wastes as inputs for materials from other industries is a productive strategy that has been developed in recent decades [46][47][48][49][50]. Initially recognized as recycling strategies and studied through economic or life cycle cost (LCC) analysis, they are nowadays associated with circular economy strategies and studied using life cycle assessment (LCA).…”
mentioning
confidence: 99%
“…It was reported that around 50,000 tons of shell waste from the seafood industry are produced per year [ 12 ]. This shell waste can pollute the area where the waste is discarded because of a bad smell from decomposing of residual attached meat on the molluscan shell [ 13 ]. Furthermore, some discarded shells are dumped in landfill or in the sea.…”
Section: Introductionmentioning
confidence: 99%
“…The recycling of shellfish wastes [ 12 ] generated by the development of marine resources is rare, despite millions of tons of shell wastes being produced and abandoned in landfills in China every year [ 13 ]. These landfilled shells leach heavy metals from the heap due to severe land and air pollution emissions during microbial decomposition and weathering.…”
Section: Introductionmentioning
confidence: 99%